Peggy and Anne Murray posing in their ballerina costumes at the MacJannet School, ca. 1930 - Associated Press of Great Britain, Ltd. (Tufts Archival Research Center, 2005)
4x7; taken from MS024:007-095#016 - "MacJannet School"